2018
DOI: 10.1111/ncmr.12135
|View full text |Cite
|
Sign up to set email alerts
|

Explaining Differences in Men and Women's Use of Unethical Tactics in Negotiations

Abstract: Emerging evidence suggests that competitiveness and empathy explain men's greater willingness to use unethical tactics in negotiations. We tested whether and how robustly they do with three distinct studies, run with three distinct populations. Simultaneous mediation analyses generally, but not completely, confirmed our expectations. In Study 1, only competitiveness mediated sex differences in unethical negotiation tactics among Chilean business students. Although empathy also explained willingness to use unet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
16
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 67 publications
1
16
0
1
Order By: Relevance
“…For instance, Kray and Haselhuhn (2012) and Lee et al (2017), despite basing their hypothesis on distinct theoretical perspectives-motivated cognition and evolutionary theory, respectively-both reported results suggesting that competitiveness explains men's willingness to lie and stretch other ethical bounds in negotiations. Pierce and Thompson (2018) directly tested this proposition and confirmed that competitiveness partly mediates this sex difference.…”
Section: Competitiveness As a Gendered Mediatormentioning
confidence: 71%
See 3 more Smart Citations
“…For instance, Kray and Haselhuhn (2012) and Lee et al (2017), despite basing their hypothesis on distinct theoretical perspectives-motivated cognition and evolutionary theory, respectively-both reported results suggesting that competitiveness explains men's willingness to lie and stretch other ethical bounds in negotiations. Pierce and Thompson (2018) directly tested this proposition and confirmed that competitiveness partly mediates this sex difference.…”
Section: Competitiveness As a Gendered Mediatormentioning
confidence: 71%
“…The Mediating Role of Gender McCabe et al (2006) theorized and provided preliminary evidence that psychological gender mediates the relation between biological sex and ethicality. Pierce and Thompson (2018) further qualified this mediating role of gender. More specifically, they proposed and confirmed hypotheses that two factors associated with psychological gender-competitiveness (expressed more strongly by men) and empathy (expressed more strongly by women)-provide a parsimonious explanation for men's greater willingness to stretch ethical boundaries in negotiations.…”
mentioning
confidence: 74%
See 2 more Smart Citations
“…Remarkable research was conducted in the field of communication [10]. Explaining the differences between men and women in using unethical tactics for negotiation.…”
Section: Introduction and Social Aspects Of The Topicality Of The Researchmentioning
confidence: 99%